Politiche della collaborazione e processi di commoning: recenti forme d’amministrazione condivisa - Caridi, Giuseppe (Scienze del Territorio, 2018)
This paper has been developed within a research perspective that aims at studying the dynamics of production of common goods, and at reflecting on the most effective forms for the activation of working methods useful for their government within the scope of planning processes.  The author critically evaluates the absolute centrality of the institutional and operational role played by local public bodies in the context of these dynamics, individuating the possible problematic nodes deriving from this condition and identifying the relative risks tied, in large part, to the exclusionary and at the same time rather inefficient nature of state bureaucratic management. Such consideration remains valid also when referring to the management of common goods promoted by private profit-oriented enterprises, regulated and operating through public procurement contracts. The author affirms that other conceptions are also viable provided that they are orientated towards a strengthening of the non-institutional sphere and its establishing dynamics. This envisages a rethinking of the very institutions the management of common goods is entrusted to. In this view, the central thesis expands the discussion to processes of direct and cooperative management of common goods by the local communities concerned. Finally, the author offers the formulation of a concrete working proposal in this perspective of shared administration.